Nursing actions with diabetes mellitus patients living in rural areas (Research, Society and Development, 2021)
Nursing care is crucial when it comes to the care of the patient affected by diabetes mellitus, as well as the development of actions, especially for those who live in rural areas because they present a particular lifestyle, in addition, they face difficulties in accessing the health service or reduced accessibility due to not living near these institutions. The aim of this study was to investigate the publications that deal with nursing actions performed with diabetes mellitus patients living in rural areas, highlighting the relevant aspects pointed out by these nursing professionals who work in the care of these people, according to scientific publications. The integrative review was used, in which 10 scientific articles available in full, in the last 5 years, selected from the Virtual Health Library, composed the analyzed sample. The results showed the relevance of the development of actions of the professional nurse in front of patients affected by diabetes mellitus and the positive results of these, show that the applicability and improvement of these actions that can be developed by professional nurses are of total relevance, both for prevention, as for dealing with the disease after it is diagnosed, especially in the rural setting where it was evidenced the need for a more special look for them.